BATIK PANDONO ABSTRAK SEBAGAI MEDIA EDUKASI DAN APRESIASI SENI: STUDI KASUS UKM BATIK PANDONO ABSTRAK DI LAWEYAN SURAKARTA - Moh. Yudik Al Faruq (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2019)
Abstract: The objectives of this study are: (1) Explain the right and effective learning model as a medium of education and appreciation for the community about UKM Batik Pandono Abstrak in Laweyan, Surakarta. (2) Explain the form of the work motif produced by the community through the learning model applied in the learning of Abstract Pandono Batik in Laweyan, Surakarta.